The grammar of words - Geert Booij (Oxford University Press, 2007)
Geert Booij's popular textbook examines how words are formed, compounded, and inflected in different languages. It shows how, when, and why to use methods of morphological analysis and explains how morphology relates to syntax, phonology, and semantics. The author considers the universal characteristics of morphology and how these are reflected in the workings of mind. The revised edition has been revised and updated throughout; it has a full glossary and a new chapter on the field's most notorious problem: the status of the word